2002
DOI: 10.1246/bcsj.75.853
|View full text |Cite
|
Sign up to set email alerts
|

Triethylborane-Induced Radical Reactions in Ionic Liquids

Abstract: Some triethylborane-induced radical reactions were found to proceed in ionic liquids. The reactions include atom transfer radical cyclization, hydrostannylation of alkyne, and atom transfer radical addition. Benzyl bromoacetate participated in the bromine atom transfer addition reaction to 1-octene in 1-ethyl-3-methylimidazolium tetrafluoroborate to afford the corresponding adduct in excellent yield. The facile bromine atom transfer addition in the ionic liquid indicates that the ionic liquid may have a highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Radical cyclization reaction of N , N -diallyl-2-iodoacetamide was first reported in ionic liquids by Oshima and co-workers . Triethylborane was added to amide (R = H) in IL [bmim][PF 6 ] as reaction medium and strirred under air at room temperature for 2 h. The corresponding lactam product (R = H) was extracted from the ionic liquid using ether giving 82% yield of pyrrolidin-2-one derivative, and the IL could be reused four times with a decreased yield only at the fifth cycle (67%).…”
Section: Five-membered Ringsmentioning
confidence: 99%
“…Radical cyclization reaction of N , N -diallyl-2-iodoacetamide was first reported in ionic liquids by Oshima and co-workers . Triethylborane was added to amide (R = H) in IL [bmim][PF 6 ] as reaction medium and strirred under air at room temperature for 2 h. The corresponding lactam product (R = H) was extracted from the ionic liquid using ether giving 82% yield of pyrrolidin-2-one derivative, and the IL could be reused four times with a decreased yield only at the fifth cycle (67%).…”
Section: Five-membered Ringsmentioning
confidence: 99%
“…Although radical polymerization using ionic liquids has been extensively studied [5], an examination of their feasibility for ordinary radical reactions in organic synthesis is yet to be sufficient. Yorimitsu and Oshima previously reported that iodine atom transfer reaction of alkynes can be effectively carried out using [bmim]PF 6 as a reaction medium [6]. We became interested in the use of ionic liquids for atom transfer carbonylation (ATC) reactions [7] for two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…9 Radical initiator-dependent reactivity has been noted in the three-component reaction of aldehydes, aryl amines and THF. 10 Triethylborane can also be used as a radical initiator in both ionic liquids 11 and in aqueous systems. 8,12 Triethylborane has also found application in non-radical processes, such as promoting the palladium-catalysed allylation of active methylene compounds 13 and amines 14 with unactivated allylic alcohols and the triethylboranetriggered intermolecular domino three-component Michael-aldol reaction.…”
Section: Methodsmentioning
confidence: 99%